A kind of high temperature resistant boron nitride fiber insulation paper and preparation method thereof
By combining high-temperature resistant boron nitride fibers with boron nitride powder, surface modification and ultraviolet irradiation, boron nitride fiber insulating paper with high temperature resistance, insulation, breakdown and hydrophobicity was prepared, which solved the problem of low temperature resistance of existing insulating materials at high temperatures, and achieved excellent insulation performance and long-life graphite electrodes.
Patent Information
- Application Number
- CN202411793392.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Existing insulating materials are low temperature resistant to high temperatures, fused and corrosion-free, affecting the service life and production efficiency of graphite electrodes.
Boron nitride fiber insulated paper with high temperature resistance, insulating, breakdown and hydrophobic properties are prepared by combining high temperature resistance, insulation, breakdown and hydrophobic properties through technical means such as surface modification and ultraviolet light irradiation.
It achieves insulating materials that provide excellent insulation performance at high temperatures, do not react with graphite materials, and are simple and cost-effective, extends the service life of graphite electrodes and improves production efficiency.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic fiber paper, and in particular to high-temperature resistant boron nitride fiber insulation paper and a preparation method thereof. Background Art
[0002] With the increasing demand for applications in high temperature and insulation fields, the requirements for the heat resistance, insulation, and anti-puncture performance of insulating materials are getting higher and higher. Single crystal growth furnaces conventionally use quartz sleeves for electrical insulation, but quartz materials have low temperature resistance and are easily melted on graphite electrodes, causing damage to graphite electrodes. The operation time of loading the furnace is long, affecting production efficiency; and quartz materials are easy to react with graphite electrodes and graphite carbon felt at high temperatures, causing corrosion to graphite electrodes and graphite felt, affecting service life. Boron nitride can be used for high-temperature insulating parts due to its high temperature resistance, insulation, anti-puncture and other excellent properties. Boron nitride fiber has fiber flexibility. The present invention fully combines boron nitride with boron nitride fiber to prepare flexible boron nitride insulation paper, and then winds the boron nitride insulation paper into a sleeve for use in a single crystal growth furnace, which can meet the high-temperature insulation requirements of graphite electrodes, and is non-reactive with graphite materials at high temperatures. It is simple to assemble and has reasonable cost, meets production and operation requirements, and has broad application prospects. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present invention provides a high-temperature resistant boron nitride fiber insulation paper and a preparation method thereof. The prepared high-temperature resistant boron nitride fiber insulation paper has good high-temperature resistance, flexibility, insulation, breakdown resistance and hydrophobicity.
[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0005] A method for preparing high temperature resistant boron nitride fiber insulation paper, comprising the following steps: preparing composite boron nitride fiber, preparing composite boron nitride powder, compounding, preparing composite quartz powder, preparing composite silica sol, mixing, molding, ultraviolet treatment, and drying;
[0006] The composite boron nitride fiber is prepared by mixing high aspect ratio boron nitride fiber, low aspect ratio boron nitride fiber, vinyl triethoxysilane and anhydrous ethanol, stirring at 40-50° C. and 100-300 rpm for 40-50 min, adding ammonia water, continuing stirring for 4.5-5 h, filtering, washing the filter cake with anhydrous ethanol and drying to obtain the composite boron nitride fiber;
[0007] In the preparation of the composite boron nitride fiber, the mass volume ratio of the high aspect ratio boron nitride fiber, the low aspect ratio boron nitride fiber, vinyl triethoxysilane, anhydrous ethanol, and ammonia water is 200-220 g: 52-55 g: 160-170 mL: 1800-2000 mL: 190-210 mL;
[0008] The mass concentration of the ammonia water is 25%;
[0009] The high aspect ratio boron nitride fiber has a diameter of 10 μm and a length of 1 cm;
[0010] The low aspect ratio boron nitride fiber has a diameter of 10 μm and a length of 200 μm;
[0011] The composite boron nitride powder is prepared by mixing boron nitride powder, 3-mercaptopropyltriethoxysilane, anhydrous ethanol and water, stirring at 55-65° C. at a stirring speed of 100-300 rpm for 3-4 hours, centrifuging, washing the precipitate with anhydrous ethanol and drying to obtain the composite boron nitride powder;
[0012] In the preparation of the composite boron nitride powder, the mass volume ratio of boron nitride powder, 3-mercaptopropyltriethoxysilane, anhydrous ethanol and water is 70-75g:100-110mL:1800-2000mL:700-750mL;
[0013] The particle size of the boron nitride powder is 100 nm;
[0014] The composite process comprises mixing composite boron nitride fiber, composite boron nitride powder and N,N-dimethylformamide, ultrasonically oscillating at a frequency of 20-25kHz for 30-40min at room temperature, and then mixing with benzoin dimethyl ether, stirring at a stirring speed of 300-500rpm at room temperature, irradiating with an ultraviolet lamp with a wavelength of 365nm, stirring for 1.5-2h, filtering, washing the filter cake with anhydrous ethanol and drying to obtain composite boron nitride;
[0015] In the composite, the mass volume ratio of the composite boron nitride fiber, the composite boron nitride powder, N,N-dimethylformamide, and benzoin dimethyl ether is 250-260 mL: 72-75 g: 9000-9500 mL: 13-15 g;
[0016] The composite quartz powder is prepared by mixing anhydrous ethanol and polyvinyl pyrrolidone, stirring at 45-50° C. and a stirring speed of 300-400 rpm for 10-15 minutes, adding quartz powder, continuing to stir for 20-30 minutes, adding water and tetraethyl orthosilicate, continuing to stir for 20-30 minutes, adding ammonia water dropwise, continuing to stir for 5-5.5 hours after the addition is completed, adding vinyl triethoxysilane, continuing to stir for 2-2.5 hours, centrifuging, washing the precipitate with anhydrous ethanol and drying, to obtain the composite quartz powder;
[0017] In the preparation of the composite quartz powder, the mass volume ratio of anhydrous ethanol, polyvinyl pyrrolidone, quartz powder, water, tetraethyl orthosilicate, ammonia water, and vinyl triethoxysilane is 1800-2000mL:7-8g:110-120g:30-35mL:37-40mL:46-50mL:4.5-5mL;
[0018] The mass concentration of the ammonia water is 25%;
[0019] The dropping speed of the ammonia water is 3-4 mL / min;
[0020] The particle size of the quartz powder is 100 nm;
[0021] The composite silica sol is prepared by mixing anhydrous ethanol, water, polyvinyl pyrrolidone and tetraethyl orthosilicate, stirring at 45-50° C. and a stirring speed of 300-400 rpm for 20-30 min, dropping ammonia water, continuing to stir for 5-5.5 h after the dropping is completed, adding vinyl triethoxysilane, continuing to stir for 2-2.5 h, centrifuging, washing the precipitate with anhydrous ethanol and drying to obtain the composite silica sol;
[0022] In the preparation of the composite silica sol, the mass volume ratio of anhydrous ethanol, water, polyvinyl pyrrolidone, tetraethyl orthosilicate, ammonia water, and vinyl triethoxysilane is 1800-2000mL:30-35mL:6-7g:37-40mL:46-50mL:4.5-5mL;
[0023] The mass concentration of the ammonia water is 25%;
[0024] The dropping speed of the ammonia water is 3-4 mL / min;
[0025] The mixing comprises mixing composite boron nitride, composite quartz powder, composite silica sol, polyethylene glycol 400, polyvinyl alcohol 1788, polyvinyl pyrrolidone, benzoin dimethyl ether and water, and stirring at a stirring speed of 300-500 rpm for 1-1.5 hours at room temperature to obtain a mixture;
[0026] In the mixture, the mass volume ratio of composite boron nitride, composite quartz powder, composite silica sol, polyethylene glycol 400, polyvinyl alcohol 1788, polyvinyl pyrrolidone, benzoin dimethyl ether, and water is 190-200g:11-14g:19-22g:4.5-5g:3-4g:1.4-1.6g:13-15g:3700-4000mL;
[0027] The molding comprises laying the filter cloth on a paper sheet former, placing a mold on the cloth, pouring the mixture into the paper sheet former, performing vacuum filtration molding, controlling the vacuum degree in the vacuum filtration molding to be 0.04-0.09 MPa, and then drying at 105-110° C. to obtain a primary model;
[0028] The ultraviolet treatment is to irradiate the primary model with an ultraviolet lamp having a wavelength of 365 nm at 40-45° C. for 2.5-3 hours to obtain a secondary model;
[0029] The drying comprises drying the secondary model at 70-80° C. for 1-1.5 h, drying at 110-120° C. for 1-1.5 h, and drying at 140-150° C. for 1.5-2 h to obtain high temperature resistant boron nitride fiber insulation paper.
[0030] A high temperature resistant boron nitride fiber insulation paper prepared by the aforementioned preparation method.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The preparation method of the high temperature resistant boron nitride fiber insulation paper of the present invention comprises the following steps: firstly, using vinyl triethoxysilane to perform surface modification on high aspect ratio boron nitride fiber and low aspect ratio boron nitride fiber to obtain composite boron nitride fiber grafted with vinyl; then, using 3-mercaptopropyl triethoxysilane to perform surface modification on boron nitride powder to obtain composite boron nitride powder grafted with thiol; then, the composite boron nitride fiber, composite boron nitride powder and benzoin dimethyl ether are mixed and irradiated with ultraviolet light and stirred; during the stirring process, the composite boron nitride powder is adsorbed on the surface of the composite boron nitride fiber; the thiol on the surface of the composite boron nitride powder reacts with the vinyl on the surface of the composite boron nitride fiber to perform thiol-ene click reaction to obtain a boron nitride fiber with a surface composited with boron nitride powder, i.e., composite boron nitride; then, the quartz powder is added to the silica sol to coat the surface with diisocyanate; After silicon oxide, vinyl triethoxysilane is used for surface modification, vinyl is grafted, and composite quartz powder with a core of quartz powder, a middle layer of silicon dioxide, and an outermost layer of vinyl is obtained. The quartz in the core can improve the insulation, the silicon dioxide in the middle layer has heat insulation, and can improve the high temperature resistance of quartz. The vinyl in the outermost layer can improve the dispersibility of quartz. Then, silica sol is mixed with vinyl triethoxysilane to obtain silica sol with vinyl grafted on the surface. Finally, composite boron nitride, composite quartz powder, and composite silica sol are mixed, molded, and then ultraviolet treatment is performed. During the ultraviolet treatment, vinyl and thiol continue to undergo thiol-ene click reaction, thereby increasing the internal crosslinking density, and sulfur atoms can also be introduced, thereby obtaining boron nitride fiber insulation paper with good high temperature resistance, flexibility, insulation, breakdown resistance, and hydrophobicity;
[0033] (2) The method for preparing high temperature resistant boron nitride fiber insulation paper of the present invention has good insulation properties and a surface resistivity of 6.3×10 15 -6.7×10 15 Ω·cm;
[0034] (3) The method for preparing high temperature resistant boron nitride fiber insulation paper of the present invention has good hydrophobicity and a water contact angle of 138.5-140.7°;
[0035] (4) The method for preparing the high temperature resistant boron nitride fiber insulation paper of the present invention has good flexibility. After the high temperature resistant boron nitride fiber insulation paper prepared by the present invention is folded in half, there is no crack at the folding line;
[0036] (5) The method for preparing high temperature resistant boron nitride fiber insulation paper of the present invention has good high temperature resistance. The high temperature resistant boron nitride fiber insulation paper prepared by the present invention is placed in an environment with a temperature of 400°C. After 30 minutes, the surface resistivity is 6.1×10 15 -6.4×10 15 Ω·cm;
[0037] (4) The preparation method of the high temperature resistant boron nitride fiber insulation paper of the present invention has good breakdown resistance. When the test method is direct current, the breakdown voltage of the high temperature resistant boron nitride fiber insulation paper prepared by the present invention is 3.584-4.488kV, the breakdown current is 5-5.11mA, and the breakdown strength is 7.690-9.951kV / mm. DETAILED DESCRIPTION
[0038] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0039] Example 1
[0040] A method for preparing high temperature resistant boron nitride fiber insulation paper, specifically comprising:
[0041] 1. Preparation of composite boron nitride fiber: 200 g of high aspect ratio boron nitride fiber, 52 g of low aspect ratio boron nitride fiber, 160 mL of vinyl triethoxysilane, and 1800 mL of anhydrous ethanol were mixed, stirred at 40 ° C at a stirring speed of 100 rpm for 40 min, 190 mL of ammonia water was added, and stirring was continued for 4.5 h, filtered, and the filter cake was washed with anhydrous ethanol and dried to obtain composite boron nitride fiber;
[0042] The mass concentration of the ammonia water is 25%;
[0043] The high aspect ratio boron nitride fiber has a diameter of 10 μm and a length of 1 cm;
[0044] The low aspect ratio boron nitride fiber has a diameter of 10 μm and a length of 200 μm;
[0045] 2. Preparation of composite boron nitride powder: 70 g of boron nitride powder, 100 mL of 3-mercaptopropyltriethoxysilane, 1800 mL of anhydrous ethanol, and 700 mL of water were mixed, stirred at 55 ° C at a stirring speed of 100 rpm for 3 h, centrifuged, and the precipitate was washed with anhydrous ethanol and then dried to obtain composite boron nitride powder;
[0046] The particle size of the boron nitride powder is 100 nm;
[0047] 3. Compounding: 250 g of composite boron nitride fiber, 72 g of composite boron nitride powder, and 9000 mL of N,N-dimethylformamide were mixed, ultrasonically shaken at a frequency of 20 kHz for 30 min at room temperature, and then mixed with 13 g of benzoin dimethyl ether, stirred at a stirring speed of 300 rpm at room temperature, and irradiated with an ultraviolet lamp with a wavelength of 365 nm, stirred for 1.5 h, filtered, and the filter cake was washed with anhydrous ethanol and dried to obtain composite boron nitride;
[0048] 4. Preparation of composite quartz powder: 1800 mL of anhydrous ethanol and 7 g of polyvinyl pyrrolidone were mixed, stirred at 45 ° C at a stirring speed of 300 rpm for 10 min, 110 g of quartz powder was added, and stirring was continued for 20 min, 30 mL of water and 37 mL of tetraethyl orthosilicate were added, and stirring was continued for 20 min, 46 mL of ammonia water was added dropwise, and the dropping speed was controlled to 3 mL / min. After the addition was completed, stirring was continued for 5 h, 4.5 mL of vinyl triethoxysilane was added, and stirring was continued for 2 h, centrifuged, and the precipitate was washed with anhydrous ethanol and dried to obtain composite quartz powder;
[0049] The mass concentration of the ammonia water is 25%;
[0050] The particle size of the quartz powder is 100 nm;
[0051] 5. Preparation of composite silica sol: 1800 mL of anhydrous ethanol, 30 mL of water, 6 g of polyvinyl pyrrolidone, and 37 mL of tetraethyl orthosilicate were mixed, stirred at 45 ° C at a stirring speed of 300 rpm for 20 min, 46 mL of ammonia water was added dropwise, and the dropping speed was controlled to 3 mL / min. After the addition was completed, stirring was continued for 5 h, 4.5 mL of vinyl triethoxysilane was added, stirring was continued for 2 h, centrifuged, and the precipitate was washed with anhydrous ethanol and dried to obtain a composite silica sol;
[0052] The mass concentration of the ammonia water is 25%;
[0053] 6. Mixing: 190 g of composite boron nitride, 11 g of composite quartz powder, 19 g of composite silica sol, 4.5 g of polyethylene glycol 400, 3 g of polyvinyl alcohol 1788, 1.4 g of polyvinyl pyrrolidone, 13 g of benzoin dimethyl ether, and 3700 mL of water were mixed, and stirred at room temperature at a stirring speed of 300 rpm for 1 h to obtain a mixture;
[0054] 7. Molding: Spread the filter cloth on the paper sheet former, place the mold on it, pour the mixture into it for vacuum filtration molding, control the vacuum degree in the vacuum filtration molding to 0.04MPa, and then dry it at 105℃ to obtain a primary model;
[0055] 8. Ultraviolet treatment: irradiate the primary model with an ultraviolet lamp with a wavelength of 365nm at 40℃ for 2.5h to obtain a secondary model;
[0056] 9. Drying: Dry the secondary model at 70°C for 1 hour, at 110°C for 1 hour, and at 140°C for 1.5 hours to obtain high temperature resistant boron nitride fiber insulation paper.
[0057] The thickness of the high temperature resistant boron nitride fiber insulation paper is 0.451 mm.
[0058] This embodiment also provides a high temperature resistant boron nitride fiber insulation paper prepared by the aforementioned preparation method.
[0059] Example 2
[0060] A method for preparing high temperature resistant boron nitride fiber insulation paper, specifically comprising:
[0061] 1. Preparation of composite boron nitride fiber: 210 g of high aspect ratio boron nitride fiber, 54 g of low aspect ratio boron nitride fiber, 165 mL of vinyl triethoxysilane, and 1900 mL of anhydrous ethanol were mixed, stirred at 45 ° C at a stirring speed of 200 rpm for 45 min, 200 mL of ammonia water was added, and stirring was continued for 4.5 h, filtered, and the filter cake was washed with anhydrous ethanol and dried to obtain composite boron nitride fiber;
[0062] The mass concentration of the ammonia water is 25%;
[0063] The high aspect ratio boron nitride fiber has a diameter of 10 μm and a length of 1 cm;
[0064] The low aspect ratio boron nitride fiber has a diameter of 10 μm and a length of 200 μm;
[0065] 2. Preparation of composite boron nitride powder: 72 g of boron nitride powder, 105 mL of 3-mercaptopropyltriethoxysilane, 1900 mL of anhydrous ethanol, and 720 mL of water were mixed, stirred at 60 ° C at a stirring speed of 200 rpm for 3.5 h, centrifuged, and the precipitate was washed with anhydrous ethanol and then dried to obtain composite boron nitride powder;
[0066] The particle size of the boron nitride powder is 100 nm;
[0067] 3. Compounding: 255 g of composite boron nitride fiber, 74 g of composite boron nitride powder, and 9200 mL of N,N-dimethylformamide were mixed, ultrasonically vibrated at a frequency of 25 kHz for 35 min at room temperature, and then mixed with 14 g of benzoin dimethyl ether, stirred at a stirring speed of 400 rpm at room temperature, and irradiated with an ultraviolet lamp with a wavelength of 365 nm, stirred for 1.5 h, filtered, and the filter cake was washed with anhydrous ethanol and dried to obtain composite boron nitride;
[0068] 4. Preparation of composite quartz powder: 1900 mL of anhydrous ethanol and 7.5 g of polyvinyl pyrrolidone were mixed, stirred at 45 ° C at a stirring speed of 350 rpm for 12 min, 115 g of quartz powder was added, and stirring was continued for 25 min, 32 mL of water and 38 mL of tetraethyl orthosilicate were added, and stirring was continued for 25 min, 48 mL of ammonia water was added dropwise, and the dropping speed was controlled to 3 mL / min. After the addition was completed, stirring was continued for 5 h, 4.8 mL of vinyl triethoxysilane was added, and stirring was continued for 2.5 h, centrifuged, and the precipitate was washed with anhydrous ethanol and dried to obtain composite quartz powder;
[0069] The mass concentration of the ammonia water is 25%;
[0070] The particle size of the quartz powder is 100 nm;
[0071] 5. Preparation of composite silica sol: 1900 mL of anhydrous ethanol, 32 mL of water, 6.5 g of polyvinyl pyrrolidone, and 38 mL of tetraethyl orthosilicate were mixed, stirred at 47 ° C at a stirring speed of 350 rpm for 25 min, 48 mL of ammonia water was added dropwise, and the dropping speed was controlled to 3 mL / min. After the addition was completed, stirring was continued for 5 h, 4.7 mL of vinyl triethoxysilane was added, stirring was continued for 2.5 h, centrifuged, and the precipitate was washed with anhydrous ethanol and dried to obtain a composite silica sol;
[0072] The mass concentration of the ammonia water is 25%;
[0073] 6. Mixing: 195 g of composite boron nitride, 12 g of composite quartz powder, 20 g of composite silica sol, 4.8 g of polyethylene glycol 400, 3.5 g of polyvinyl alcohol 1788, 1.5 g of polyvinyl pyrrolidone, 14 g of benzoin dimethyl ether, and 3800 mL of water were mixed, and stirred at room temperature at a stirring speed of 400 rpm for 1.5 h to obtain a mixture;
[0074] 7. Molding: Spread the filter cloth on the paper sheet former, place the mold on it, pour the mixture into it for vacuum filtration molding, control the vacuum degree in the vacuum filtration molding to 0.07MPa, and then dry it at 105℃ to obtain a primary model;
[0075] 8. Ultraviolet treatment: irradiate the primary model with an ultraviolet lamp with a wavelength of 365nm at 42°C for 2.5 hours to obtain a secondary model;
[0076] 9. Drying: Dry the secondary model at 75°C for 1.5 h, at 115°C for 1.5 h, and at 145°C for 1.5 h to obtain high temperature resistant boron nitride fiber insulation paper.
[0077] The thickness of the high temperature resistant boron nitride fiber insulation paper is 0.465 mm.
[0078] This embodiment also provides a high temperature resistant boron nitride fiber insulation paper prepared by the aforementioned preparation method.
[0079] Example 3
[0080] A method for preparing high temperature resistant boron nitride fiber insulation paper, specifically comprising:
[0081] 1. Preparation of composite boron nitride fiber: 220 g of high aspect ratio boron nitride fiber, 55 g of low aspect ratio boron nitride fiber, 170 mL of vinyl triethoxysilane, and 2000 mL of anhydrous ethanol were mixed, stirred at 50 ° C at a stirring speed of 300 rpm for 50 min, 210 mL of ammonia water was added, and stirring was continued for 5 h. The filter cake was washed with anhydrous ethanol and then dried to obtain a composite boron nitride fiber;
[0082] The mass concentration of the ammonia water is 25%;
[0083] The high aspect ratio boron nitride fiber has a diameter of 10 μm and a length of 1 cm;
[0084] The low aspect ratio boron nitride fiber has a diameter of 10 μm and a length of 200 μm;
[0085] 2. Preparation of composite boron nitride powder: 75 g of boron nitride powder, 110 mL of 3-mercaptopropyltriethoxysilane, 2000 mL of anhydrous ethanol, and 750 mL of water were mixed, stirred at 65 ° C at a stirring speed of 300 rpm for 4 h, centrifuged, and the precipitate was washed with anhydrous ethanol and then dried to obtain composite boron nitride powder;
[0086] The particle size of the boron nitride powder is 100 nm;
[0087] 3. Compounding: 260 g of composite boron nitride fiber, 75 g of composite boron nitride powder, and 9500 mL of N,N-dimethylformamide were mixed, ultrasonically shaken at a frequency of 25 kHz for 40 min at room temperature, and then mixed with 15 g of benzoin dimethyl ether, stirred at a stirring speed of 500 rpm at room temperature, and irradiated with an ultraviolet lamp with a wavelength of 365 nm, stirred for 2 h, filtered, and the filter cake was washed with anhydrous ethanol and dried to obtain composite boron nitride;
[0088] 4. Preparation of composite quartz powder: 2000 mL of anhydrous ethanol and 8 g of polyvinyl pyrrolidone were mixed, stirred at 50 ° C at a stirring speed of 400 rpm for 15 min, 120 g of quartz powder was added, and stirring was continued for 30 min, 35 mL of water and 40 mL of tetraethyl orthosilicate were added, and stirring was continued for 30 min, 50 mL of ammonia water was added dropwise, and the dropping speed was controlled to 4 mL / min. After the addition was completed, stirring was continued for 5.5 h, 5 mL of vinyl triethoxysilane was added, and stirring was continued for 2.5 h, centrifuged, and the precipitate was washed with anhydrous ethanol and dried to obtain composite quartz powder;
[0089] The mass concentration of the ammonia water is 25%;
[0090] The particle size of the quartz powder is 100 nm;
[0091] 5. Preparation of composite silica sol: 2000 mL of anhydrous ethanol, 35 mL of water, 7 g of polyvinyl pyrrolidone, and 40 mL of tetraethyl orthosilicate were mixed, and stirred at 400 rpm for 30 min at 50 ° C, 50 mL of ammonia water was added dropwise, and the dropping speed was controlled to 4 mL / min. After the addition was completed, stirring was continued for 5.5 h, 5 mL of vinyl triethoxysilane was added, and stirring was continued for 2.5 h. Centrifugation was performed, and the precipitate was washed with anhydrous ethanol and dried to obtain a composite silica sol;
[0092] The mass concentration of the ammonia water is 25%;
[0093] 6. Mixing: 200 g of composite boron nitride, 14 g of composite quartz powder, 22 g of composite silica sol, 5 g of polyethylene glycol 400, 4 g of polyvinyl alcohol 1788, 1.6 g of polyvinyl pyrrolidone, 15 g of benzoin dimethyl ether, and 4000 mL of water were mixed, and stirred at room temperature at a stirring speed of 500 rpm for 1.5 h to obtain a mixture;
[0094] 7. Molding: Spread the filter cloth on the paper sheet former, place the mold on it, pour the mixture into it for vacuum filtration molding, control the vacuum degree in the vacuum filtration molding to 0.09MPa, and then dry it at 110℃ to obtain a primary model;
[0095] 8. Ultraviolet treatment: irradiate the primary model with an ultraviolet lamp with a wavelength of 365nm at 45°C for 3 hours to obtain a secondary model;
[0096] 9. Drying: Dry the secondary model at 780°C for 1.5h, at 120°C for 1.5h, and at 150°C for 2h to obtain high temperature resistant boron nitride fiber insulation paper.
[0097] The thickness of the high temperature resistant boron nitride fiber insulation paper is 0.466 mm.
[0098] This embodiment also provides a high temperature resistant boron nitride fiber insulation paper prepared by the aforementioned preparation method.
[0099] Performance Test 1
[0100] The surface resistivity and water contact angle of the high temperature resistant boron nitride fiber insulation paper prepared in Examples 1-3 were tested. The test results are shown in Table 1:
[0101] Table 1
[0102]
[0103] Performance Test 2
[0104] The flexibility of the high temperature resistant boron nitride fiber insulation paper prepared in Examples 1-3 was tested. The testing method was to fold the high temperature resistant boron nitride fiber insulation paper in half and observe whether there were cracks at the folding line. The observation results are shown in Table 2:
[0105] Table 2
[0106]
[0107] Performance Test 3
[0108] The high temperature resistance of the high temperature resistant boron nitride fiber insulation paper prepared in Examples 1-3 was tested. The test method was to place the high temperature resistant boron nitride fiber insulation paper in an environment with a temperature of 400° C. After 30 minutes, the surface resistivity was tested. The test results are shown in Table 3:
[0109] Table 3
[0110]
[0111] Performance Test 4
[0112] The breakdown voltage, breakdown current and breakdown strength of the high temperature resistant boron nitride fiber insulation paper prepared in Examples 1-4 were tested. The test results are shown in Table 4:
[0113] Table 4
[0114]
[0115] It can be seen from the results of performance tests 1-4 that the high temperature resistant boron nitride fiber insulation paper prepared in Example 1-3 has excellent high temperature resistance, flexibility, insulation, breakdown resistance, and hydrophobicity.
[0116] Unless otherwise specified, all percentages used in the present invention are by mass.
[0117] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing high temperature resistant boron nitride fiber insulation paper, characterized in that: The method comprises the following steps: preparing composite boron nitride fiber, preparing composite boron nitride powder, compounding, preparing composite quartz powder, preparing composite silica sol, mixing, molding, ultraviolet treatment, and drying; The method for preparing the composite boron nitride fiber comprises mixing high aspect ratio boron nitride fiber, low aspect ratio boron nitride fiber, vinyl triethoxysilane and anhydrous ethanol, stirring at 40-50° C., adding ammonia water, continuing stirring, filtering, washing the filter cake and drying to obtain the composite boron nitride fiber; In the preparation of the composite boron nitride fiber, the high aspect ratio boron nitride fiber has a diameter of 10 μm and a length of 1 cm; The low aspect ratio boron nitride fiber has a diameter of 10 μm and a length of 200 μm; The preparation of the composite boron nitride powder comprises mixing boron nitride powder, 3-mercaptopropyltriethoxysilane, anhydrous ethanol and water, stirring at 55-65° C., centrifuging, washing the precipitate and drying to obtain the composite boron nitride powder; The composite method comprises mixing composite boron nitride fiber, composite boron nitride powder and N,N-dimethylformamide, ultrasonically vibrating, and then mixing with benzoin dimethyl ether, stirring at room temperature, irradiating with an ultraviolet lamp with a wavelength of 365 nm, stirring for 1.5-2 hours, filtering, washing the filter cake with anhydrous ethanol and drying to obtain composite boron nitride; The composite quartz powder is prepared by mixing anhydrous ethanol and polyvinyl pyrrolidone, stirring at 45-50° C., adding quartz powder, continuing to stir, adding water and tetraethyl orthosilicate, continuing to stir, dropping ammonia water, continuing to stir after the dropping, adding vinyl triethoxysilane, continuing to stir, centrifuging, washing the precipitate and drying to obtain the composite quartz powder; The composite silica sol is prepared by mixing anhydrous ethanol, water, polyvinyl pyrrolidone and tetraethyl orthosilicate, stirring at 45-50° C., dropping ammonia water, continuing to stir after the dropping is completed, adding vinyl triethoxysilane, continuing to stir, centrifuging, washing the precipitate and drying to obtain the composite silica sol; The mixing comprises mixing composite boron nitride, composite quartz powder, composite silica sol, polyethylene glycol 400, polyvinyl alcohol 1788, polyvinyl pyrrolidone, benzoin dimethyl ether and water, and stirring at room temperature for 1-1.5 hours to obtain a mixture; In the mixture, the mass volume ratio of composite boron nitride, composite quartz powder, composite silica sol, polyethylene glycol 400, polyvinyl alcohol 1788, polyvinyl pyrrolidone, benzoin dimethyl ether, and water is 190-200g:11-14g:19-22g:4.5-5g:3-4g:1.4-1.6g:13-15g:3700-4000mL; The forming comprises laying the filter cloth on a paper sheet former, placing a mold on the cloth, pouring the mixture into the paper sheet former, performing vacuum filtration forming, and then drying the mixture to obtain a primary mold. The ultraviolet treatment is to irradiate the primary model with an ultraviolet lamp having a wavelength of 365 nm at 40-45° C. for 2.5-3 hours to obtain a secondary model; The preparation method comprises the following steps: firstly, vinyl triethoxysilane is used to perform surface modification on high aspect ratio boron nitride fiber and low aspect ratio boron nitride fiber to obtain composite boron nitride fiber grafted with vinyl; then, 3-mercaptopropyl triethoxysilane is used to perform surface modification on boron nitride powder to obtain composite boron nitride powder grafted with mercapto groups; then, the composite boron nitride fiber, composite boron nitride powder and benzoin dimethyl ether are mixed, irradiated with an ultraviolet lamp and stirred; during the stirring process, the composite boron nitride powder is adsorbed on the surface of the composite boron nitride fiber; the mercapto groups on the surface of the composite boron nitride powder react with the vinyl groups on the surface of the composite boron nitride fiber to perform mercapto-ene click reaction to obtain the boron nitride fiber with the surface composited with boron nitride powder, i.e., composite boron nitride; then, quartz powder is added to a silicon solution to obtain the composite boron nitride fiber; In the glue, after the surface is coated with silica, vinyltriethoxysilane is used for surface modification and vinyl is grafted to obtain a composite quartz powder with a core of quartz powder, a middle layer of silica, and an outermost layer of vinyl. The quartz in the inner core can improve the insulation, the silica in the middle layer has heat insulation and can improve the high temperature resistance of quartz, and the outermost layer of vinyl can improve the dispersibility of quartz. The silica sol is then mixed with vinyltriethoxysilane to obtain a silica sol with vinyl grafted on the surface. Finally, the composite boron nitride, the composite quartz powder, and the composite silica sol are mixed, formed, and then ultraviolet treatment is performed. During the ultraviolet treatment, the vinyl and the thiol continue to undergo a thiol-ene click reaction, thereby increasing the internal crosslinking density and introducing sulfur atoms.
2. The method for preparing high temperature resistant boron nitride fiber insulation paper according to claim 1, characterized in that: In the preparation of the composite boron nitride fiber, the mass volume ratio of the high aspect ratio boron nitride fiber, the low aspect ratio boron nitride fiber, vinyl triethoxysilane, anhydrous ethanol, and ammonia water is 200-220 g: 52-55 g: 160-170 mL: 1800-2000 mL: 190-210 mL; The mass concentration of the ammonia water is 25%.
3. The method for preparing high temperature resistant boron nitride fiber insulation paper according to claim 1, characterized in that: In the preparation of the composite boron nitride powder, the mass volume ratio of boron nitride powder, 3-mercaptopropyltriethoxysilane, anhydrous ethanol and water is 70-75g:100-110mL:1800-2000mL:700-750mL; The particle size of the boron nitride powder is 100 nm.
4. The method for preparing high temperature resistant boron nitride fiber insulation paper according to claim 1, characterized in that: In the composite, the mass volume ratio of the composite boron nitride fiber, the composite boron nitride powder, N,N-dimethylformamide and benzoin dimethyl ether is 250-260 mL: 72-75 g: 9000-9500 mL: 13-15 g.
5. The method for preparing high temperature resistant boron nitride fiber insulation paper according to claim 1, characterized in that: In the preparation of the composite quartz powder, the mass volume ratio of anhydrous ethanol, polyvinyl pyrrolidone, quartz powder, water, tetraethyl orthosilicate, ammonia water, and vinyl triethoxysilane is 1800-2000mL:7-8g:110-120g:30-35mL:37-40mL:46-50mL:4.5-5mL; The mass concentration of the ammonia water is 25%; The dropping speed of the ammonia water is 3-4 mL / min; The particle size of the quartz powder is 100 nm.
6. The method for preparing high temperature resistant boron nitride fiber insulation paper according to claim 1, characterized in that: In the preparation of the composite silica sol, the mass volume ratio of anhydrous ethanol, water, polyvinyl pyrrolidone, tetraethyl orthosilicate, ammonia water, and vinyl triethoxysilane is 1800-2000mL:30-35mL:6-7g:37-40mL:46-50mL:4.5-5mL; The mass concentration of the ammonia water is 25%; The dropping speed of the ammonia water is 3-4 mL / min.
7. The method for preparing high temperature resistant boron nitride fiber insulation paper according to claim 1, characterized in that: The drying comprises drying the secondary model at 70-80° C. for 1-1.5 h, drying at 110-120° C. for 1-1.5 h, and drying at 140-150° C. for 1.5-2 h to obtain high temperature resistant boron nitride fiber insulation paper.
8. A high temperature resistant boron nitride fiber insulation paper prepared according to the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Method for preparing highly heat-conducting ceramic fiber corrugated paper
CN102561112A
High-strength computer rear cover with middle frame and processing technology of high-strength computer rear cover
CN115403805A